Securitizing Drug Tourism: Cannabis Legalization and Policy Reversal in Thailand (2019–2025) - Theresia Nelvina Putri Christanti; Laras Ayu Sekar Arum; Helena Eka Putri; Renitha Dwi Hapsari (Program Studi Ilmu Pemerintahan, FISIP - Universitas Halu Oleo, 2026)
This article examines the emergence of drug tourism in Thailand in the context of cannabis decriminalization and its securitization as a national security issue during the period 2019–2025. After Thailand’s legalize medical cannabis in 2019 and removed cannabis from Category V narcotics list in 2022, the country became the first in Southeast Asia to adopt a relatively liberal cannabis policy. This policy shift created new economic opportunities, particularly in the tourism sectors, and encourage the growth of cannabis based tourism in major destinations such as Bangkok, Chiang Mai, and Phuket. However, the rapid expansion of cannabis commercialization and consumption also raised concerns regarding public health, youth exposure, and Thailand’s international tourism image. Using the securitization theory proposed by Buzan et al., this study analyzes how drug tourism and cannabis use were reframed by the government as a social security threat. This research employs a qualitative descriptive approach based on policy documents, official reports, and media sources. The findings show that the Thailand government gradually securitized the phenomenon of drugs tourism by framing recreational cannabis use as a threat to social order and public health, which led to tighter regulations and discussion on reclassifying cannabis as a controlled substance. These findings highlight a policy dilemma between the economic benefits of tourism and the need to maintain social stability and public health. Theoritically, this study contributes to expanding the application of securitization theory in the study of drug policy and tourism in developing countries undergoing policy transitions.